Analysis of Accounting Behavior in the Preparation of Financial Reports in the Culinary Sector of MSMEs in North Sumatra - Monetarist Butar Butar (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze accounting behavior in the preparation of financial reports by culinary MSMEsin North Sumatra Province. The approach used in this study is qualitative with descriptive methods. Data wereobtained through interviews, observations, and documentation of culinary MSMEs. The results show that theaccounting behavior of MSMEs is still relatively simple and unsystematic, characterized by irregular financialrecording and the use of manual recording methods. Behavioral factors such as perception, motivation, and attitudeinfluence the preparation of financial reports. Negative perceptions of accounting as something complicated lead tolow interest in financial recording, while situational motivation and a lack of concern also affect the quality offinancial reports. The level of understanding of MSMEs regarding the importance of financial reports in accordancewith accounting standards (SAK EMKM) is also still low. In addition, there are various obstacles faced, such aslimited accounting knowledge, lack of time, the absence of separation of personal and business finances, and minimaltraining and technological support. Thus, efforts are needed to improve accounting literacy, behavioral changes, andsupport from various parties to improve the quality of MSME financial reports.